2011
DOI: 10.1002/da.20913
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and Alliance in the Treatment of Depressed, Sexually Abused Women

Abstract: Background Depression among women with sexual abuse histories is less treatment responsive than in general adult samples. One contributor to poorer treatment outcomes may be abused women’s difficulties in forming and maintaining secure relationships, as reflected in insecure attachment styles, which could also impede the development of a positive therapeutic alliance. The current study examines how attachment orientation (i.e., anxiety and avoidance) and development of the working alliance are associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 62 publications
4
23
0
6
Order By: Relevance
“…Overall, the results reveal that certain types of attachments, specifically positive peer attachments and communication within the father-child relationships were associated with greater alliance and sexual abuse trauma was associated with lower alliance. Generally, these results are consistent with psychotherapy literature and research on the relationships between alliance and anxiety-related trauma (Smith et al, 2012) and attachment (Zorzella, Muller, & Classen, 2014). One meta-analysis for example revealed associations between global attachment orientations in interpersonal relationships and therapeutic alliances (Diener, Hilsenroth, & Weinberger, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…Overall, the results reveal that certain types of attachments, specifically positive peer attachments and communication within the father-child relationships were associated with greater alliance and sexual abuse trauma was associated with lower alliance. Generally, these results are consistent with psychotherapy literature and research on the relationships between alliance and anxiety-related trauma (Smith et al, 2012) and attachment (Zorzella, Muller, & Classen, 2014). One meta-analysis for example revealed associations between global attachment orientations in interpersonal relationships and therapeutic alliances (Diener, Hilsenroth, & Weinberger, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…Other studies have also found that individuals who experience childhood sexual trauma are likely to have symptoms of depression, PTSD, anxiety, dissociations (Leserman, 2005;Smith et al, 2011). A sample of women experiencing major depression and childhood sexual abuse was assessed on their social maladjustment, depression and death ideation.…”
Section: Summary Of Major Findingsmentioning
confidence: 99%
“…Results from this study yielded those women who experience childhood sexual trauma had a high rate of suicidal behaviors. These individuals displayed higher levels of problems with social and leisure time including intimate or peer relationships (Smith et al, 2011). In addition, a review of literature found individuals who experience childhood trauma are likely to re-victimized in adulthood which also impacts overall levels of subjective well-being (Leserman, 2005).…”
Section: Summary Of Major Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some staff routinely demonstrated many interpersonal behaviors and characteristics that have been noted in the psychotherapy literature to be important to the development of a “positive therapeutic alliance,” including reflective listening, respectful and positive regard, and paying attention to the participant’s experience (34). Such characteristics are associated with positive treatment outcomes in many vulnerable populations, including substance users (3537), and may have had a similarly positive effect in this experimental setting as well.…”
Section: Discussionmentioning
confidence: 83%